Scarman and after : essays reflecting on Lord Scarman's Report, the riots, and their aftermath - Benyon, John (Pergamon Press, 1984)
Scarman and After: Essays Reflecting on Lord Scarman's Report, the Riots and their Aftermath covers the proceedings of a conference on Lord Scarman's social and economic issues, held at the University of Leicester in April 1982, organized by the Continuing Education Unit of the University's Department of Adult Education. The Lord Scarman Report itemized and stressed particular issues that arose from the Brixton disorders. This text is organized into five parts encompassing 22 chapters. The first parts explore the political agenda of the Brixton riot and Lord Scarman's report, explanations, images and impact of riots. Another part is concerned with the issues in policy making related to the community, public, and accountability. These topics are followed by discussions of the issues of unemployment and racial disadvantages in cities. The last part contains a summary of the Report. This book will prove useful to historians, sociologists, and researchers.